Study of Women's Leadership Roles and Its Effect on Middle-Countries Economy - Fathia, Syaharani Noer; Nur Susilowati, Retno Yuni; Majidah, Rona; Octary, Ayu Dwiny; Rohman, Fatkhur (Jurnal Manajemen, Akuntansi, Ekonomi, 2025)
The Sustainable Development Goals (SDGs) represent the United Nations' agenda for sustainable development, encompassing 17 objectives, with Goal 5 focusing on "Achieving Gender Equality." This goal aims to eliminate gender-based discrimination and inequality. The rate of increase in women's participation in national parliaments is notably slow, standing at only 26% over a span of seven years (2015-2022). If this sluggish pace continues, achieving SDG 5 is projected to take approximately 40 years, potentially hindering economic growth. Economic empowerment of women has the potential to accelerate this participation rate while simultaneously fostering economic growth. This research aims to examine how the significant roles of women in the context of gender equality by leading a corporation and participate on parliament able to promote economic growth in middle-income countries from 2020-2022 using panel path analysis. The findings indicate that economic growth has a significant positive impact on women's leadership role to achieve gender equality, it is essential to provide equal opportunities for women, eliminate bias and discrimination, eradicate patriarchal culture, and create work environments that support work-life balance.